Process control with recipe management system - Kalambur Rajarathinam Vadivazhagu (2008)
In a semiconductor assembly and test firm, a Recipe Management System is implemented. The system is to help to manage the process programs – called recipes, used for production for each process step. It essentially maintains master recipes in a centralized location and provides automatic upload and download of recipes.